Online Learning In Elementary School During The Covid-19 Pandemic - Vera Nita; Agustin Atakhiroh Nur Cahyaningsih; Umi Rachmawati (Prosiding University Research Colloquium, 2021)
Education is a conscious and planned effort made to create a learning atmosphere andlearning process to provide a learning experience for students. This experience consists of3 aspects, namely cognitive, affective and psychomotor. This research was motivated bythe impact of the COVID-19 pandemic, which impacted the health and economic sectorsand the education sector. Therefore, the learning process for primary school education iscurrently carried out remotely or online by utilizing learning media. This research isqualitative research with a case study type. The data sources were obtained from 2research samples: the Sidorejo State Elementary School (village) and the Tempurejo 1State Primary School (urban) from the Magelang area, which learned in the epidemic era.The technique used is the interview. The results showed that elementary schools locatedin cities were easier to carry out bold learning. In contrast, in village schools, the practicallearning process was carried out offline, which could help students in the learning process.There were several obstacles such as unstable internet networks or even the unavailabilityof mobile phones to implement teaching-learning boldly.